Grammarly as a Tool to Enhance Students' Self-Directed Learning - Halim, Abdul; Sharina, Sharina; Zur, Sarjaniah (KnE Social Sciences, 2022)
The goal of this study was to examine whether Grammarly can help students improve their self-directed learning in L2 writing. Qualitative research methods were used. Data were collected from 20 students in the third semester of the English Education Study Program at IAIN Kendari using questionnaires, reflections, and interviews. According to the findings, Grammarly aided students’ self-directed learning by educating them on the benefits of using Grammarly to improve their writing quality and encouraging them to self-evaluate their progress. Based on the results, lecturers and prospective teachers should use a helpful technology like Grammarly to help students improve their writing Keywords: Grammarly, self-directed learning, L2 writing